Juridical Analysis of the Application of Law (Restorative Justice) towards Children in Obscenity Cases (Case Study Decision No: 2690/Pid.Sus/2015/Pn.Mdn) - Hasibuan, Suhaily Amri; Warman, Edi; Marlina, Marlina; Rafiqi, Rafiqi (Universitas Medan Area, 2023)
The principles of child protection, especially the principle of non-discrimination and the rights of children, including those involved in criminal acts, are the focus of this research. Research questions include legal arrangements in the juvenile justice process, obstacles faced by restorative justice in law enforcement in Indonesia, and the application of restorative justice in resolving criminal cases in Indonesian criminal law. This type of research is normative juridical, which analyzes normative provisions related to restorative justice in Indonesia. The purpose of this research is to examine regulations that protect crime victims. The results show that restorative justice in handling juvenile crimes is important in improving relationships between perpetrators, victims, and society. A restorative justice process emphasizes the importance of fulfilling the rights of victims and society. The principles of restorative justice and diversion in law enforcement against children have been regulated in Law Number 11 of 2012 concerning the juvenile justice system.